Health professional's perception of a smoking cessation intervention among disadvantaged patients participating in a pragmatic randomized trial - Aurélia Manns; Sarah Mahdjoub; Gladys Ibanez; Emilie Jarrier; Ava Daeipour; Maria Melchior; Fabienne El-Khoury (BMC, 2023)
Abstract Introduction Individuals who have a low socio-economic position (SEP) are more likely to smoke and face greater barriers to quitting tobacco. However, the effectiveness of tailored interventions has been limited probably due to specific challenges relative to this population. We conducted a mixed-method study to better understand health professionals' perceptions and barriers when implementing a preference-based smoking cessation (SC) intervention among disadvantaged smokers. Methods A self-administered online questionnaire was sent to health professionals (doctors' and other health professionals specialized in SC) participating in "STOP" a pragmatic multicentre randomized controlled trial. Perceptions regarding patient eligibility, the doctor-patient relationship, general study organization, and satisfaction were measured. Results Twenty-eight STOP study investigators responded. Health professionals prioritize smoking cessation for disadvantaged patients, but face challenges in approaching and following them. A research intervention providing cessation tools based on preference was deemed useful but generally undermined by time constraints. Health professionals' preconceptions regarding patients in low SEP having other "pressing problems" which might be exacerbated by quitting smoking were also identified. Further, participation in a research intervention was perceived as not satisfactory due to workload and lack of time. Conclusion Our results highlight general barriers inherent to implementing pragmatic trials. They also present specific challenges in smoking cessation trials among disadvantaged population, essential to advance equity in tobacco control.